Pengaruh Dokumen Perencanaan Dan Kompetensi Sumber Daya Manusia Terhadap Penyerapan Anggaran Pada Dinas Pekerjaan Umum Kabupaten Bone Bolango - Saprudin Saprudin (Universitas Gorontalo, 2018)
The problem of budget absorption at the Public Works Department of Bone Bolango Regency is still relatively low. Because in the implementation programs tend to accumulate at the end of the year, this is caused by a plan that is not conceptualized well and less competent human resources in terms of good service field of work done. So that, impact on the implementation and results are not maximal.The study aims to determine how the influence of planning dokuments and competence of human resources on the absorption of the budget at the Department of Public Works Bone Bolango Regency. The resultd showed that the planning dokuments and competence of human resources have a positive and significant impact on the budget absorption, either partially or simultaneously.The result of determination coefficient test shows that the absorption of existing budget at the Public Works Department of Bone Bolango Regency is influenced by the variable of planning document and human resource competence of 43,3% and the rest 56,7% influenced by other variable not examined in this research, between Other administrative records, procurement documents, and inventory money.